Freezing and thawing effects on fat, protein, and lactose levels of human natural milk administered by gavage and continuous infusion - Andrea D. Abranches; Fernanda V.M. Soares; Saint Clair G. Junior; Maria Elisabeth L. Moreira (Brazilian Society of Pediatrics, 2014)
Objectives: to analyze the changes in human milk macronutrients: fat, protein, and lactose in natural human milk (raw), frozen and thawed, after administration simulation by gavage and continuous infusion. Method: an experimental study was performed with 34 human milk samples. The infrared spectrophotometry using the infrared analysis equipment MilkoScan Minor® (Foss, Denmark) equipment was used to analyze the macronutrients in human milk during the study phases. The analyses were performed in natural (raw) samples and after freezing and fast thawing following two steps: gavage and continuous infusion. The non‐parametric Wilcoxon test for paired samples was used for the statistical analysis. Results: the fat content was significantly reduced after administration by continuous infusion (p < 0.001) during administration of both raw and thawed samples. No changes in protein and lactose content were observed between the two forms of infusion. However, the thawing process significantly increased the levels of lactose and milk protein. Conclusion: the route of administration by continuous infusion showed the greatest influence on fat loss among all the processes required for human milk administration.